THE INFLUENCES OF A RECESSION ON THE STRATEGIES OF A BORN GLOBAL AND A CONVENTIONAL COMPANY - Siivonen, Heidi (My University, 2016)
The global market is continuously facing changes, which has an impact on the business of companies of this market arena. Recession has been a hot topic for the past years and especially the consequences of the great recession are still present. Nevertheless, the globalization has offered new possibilities for companies and the amount of born global companies are increasing all the time. However, both born global companies and conventional companies are facing the same external forces, where recession is one of them. It has been researched that companies change their strategies when recession occurs but there is no general consensus about these changes, moreover, there is scarce research on the strategic changes of born global companies. Therefore, the purpose of the study is to investigate how the strategic changes during recession differ among the born global and the conventional company. The theoretical framework of the study includes theories about strategic change and especially its content. Also, the previous research on the strategic changes in response to recession is used. In addition, the concept of strategic fit is an important part of the external environment and strategic change. The empirical material was gathered from two companies by interviewing two representatives of each company. Other documentary were used as well. The companies were chosen from the health technology industry; the other one was born global and the other a conventional company. Therefore, the method used in the study is qualitative and also a comparative case study. The findings of the study show that both, conventional and born global company, changed their strategies during recession. However, the scale of the changes was much higher in the born global company than in the conventional company. It was also found in the study that both companies chose defensive strategies during recession whereas the previous literature suggests that small companies would use growth strategies during recession. Nevertheless, the empirical findings support the fact that companies do change their strategies when they are confronted with recession.
Keywords: Strategic management; great recession; strategic change; born global; strategic fit; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in Strategic Management|